Binary Aquila Optimizer with Taper-Shaped Transfer Function: An Application for Merkle-Hellman Knapsack Cryptosystems - Yıldızdan, Gülnur (Intelligent Methods In Engineering Sciences, 2025)
Metaheuristic algorithms are powerful methods used to solve large and complex optimization problems. Thanks to their flexibility, they provide effective results in various fields and also have an important place in security applications such as the Merkle-Hellman Knapsack Crypto System. Aquila Optimizer is an optimization algorithm inspired by the hunting behavior of aquilas. It provides fast and effective solutions to complex problems. In this study, Aquila Optimizer is discretized using taper-shaped transfer functions. Taper-shaped transfer functions help the algorithm obtain more precise and effective results by increasing its performance. Four BinAO versions obtained in this way were tested on the Merkle-Hellman Knapsack Cryptosystem. In the tests conducted for the cryptanalysis of "CAT" and "MACRO" messages, the version achieved more successful results. Additionally, tests conducted with the algorithms in the literature clearly showed that the proposed algorithm is successful and effective.